Computational study of kaurene diterpenoids for antivirals against SARS-CoV-2 - Nurlela Nurlela,, Fikry Awaluddin, Irmanida Batubara,, Setyanto Tri Wahyudi (Journal of Applied Pharmaceutical Science, 2022)
Kaurene diterpenoids were found in some plants such as Adenostemma lavenia and Pteris semipinnata to have antioxidant, antiinflammatory, anticancer, antitumor, cytotoxic, and antiviral activities. To evaluate the potency of kaurene diterpenoids as antivirals against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), we conducted an in silico study of several kaurene diterpenoids and antiviral drugs such as remdesivir and favipiravir in inhibition essential SARS-CoV-2 proteins including 3CLpro, Plpro, nucleocapsid (N), and membrane (M) through molecular docking, molecular dynamic (MD) simulations, adsorption, distribution, metabolism, excretion, and toxicity (ADMET), and pharmacokinetic properties prediction using a number of pieces of software. The docking study showed that the kaurene diterpene glycosides have a higher binding affinity to the 3CLpro, N, and M proteins of SARS-CoV-2 than other kaurene diterpenoids and even antiviral drugs such as remdesivir and favipiravir. Inhibition of these nonstructural and structural proteins has a significant impact on disrupting the viral replication and viral assembly of SARS-CoV-2. Almost all the complexes showed minimum deviation and fluctuation, indicating that each ligand is strongly bound to the binding site of proteins. ADMET prediction revealed all kaurene diterpenoids were well absorbed by the human intestine, noncarcinogenic, and did not cause mutations in DNA. Therefore, we expected these materials could be a potential preventive and therapeutic agent in the fight against the COVID-19 disease.
Keywords: Kaurene diterpenoids, glycoside, inhibitor, in silico, COVID-19, health